2010
DOI: 10.3348/kjr.2010.11.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast Enhanced Magnetic Resonance Imaging of Diffuse Spinal Bone Marrow Infiltration in Patients with Hematological Malignancies

Abstract: ObjectiveTo investigate the significance of the dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) parameters of diffuse spinal bone marrow infiltration in patients with hematological malignancies.Materials and MethodsDynamic gadolinium-enhanced MR imaging of the lumbar spine was performed in 26 patients with histologically proven diffuse bone marrow infiltration, including multiple myeloma (n = 6), acute lymphoblastic leukemia (n = 6), acute myeloid leukemia (n = 5), chronic myeloid leukemia (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Regardless of the analysis methods, most studies found DCE parameters showing significant differences between diseased and normal bone marrow, or between different lesions(815). Khadem et al used heuristic DCE analysis to discriminate hypervascular from hypovascular spinal metastases (12), and later Saha et al from the same research group showed that pharmacokinetic parameters analyzed by using a commercial software (NordicNeuroLab) could distinguish hypervascular renal cell carcinoma from hypovascular prostate carcinoma (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the analysis methods, most studies found DCE parameters showing significant differences between diseased and normal bone marrow, or between different lesions(815). Khadem et al used heuristic DCE analysis to discriminate hypervascular from hypovascular spinal metastases (12), and later Saha et al from the same research group showed that pharmacokinetic parameters analyzed by using a commercial software (NordicNeuroLab) could distinguish hypervascular renal cell carcinoma from hypovascular prostate carcinoma (13).…”
Section: Discussionmentioning
confidence: 99%
“…Khadem et al used heuristic DCE analysis to discriminate hypervascular from hypovascular spinal metastases (12), and later Saha et al from the same research group showed that pharmacokinetic parameters analyzed by using a commercial software (NordicNeuroLab) could distinguish hypervascular renal cell carcinoma from hypovascular prostate carcinoma (13). DCEMRI using heuristic analysis and model fitting has been applied to characterize vascular properties of different hematologic malignancies (eg, myeloma and lymphoma) with different grades of bone marrow involvement (8,9,15). We have shown that DCE parameters of metastatic cancers were significantly different from those of myeloma (10) and inflammatory TB (11).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Alterations of dynamic contrast enhancement with diffuse malignant bone marrow infiltration have been described. [19][20][21] Numerous studies have focused on the use of DCE-MRI as a tool for evaluating bone marrow in hematologic malignancies. 19,20,[22][23][24] Chen et al evaluated the use of DCE-MRI of bone marrow as a predictor of survival for patients with acute myeloid leukemia who were clinically in complete remission and found that the perfusion kinetics of the bone marrow were an indicator of survival.…”
Section: Gadolinium Contrast-enhanced Mrimentioning
confidence: 99%
“…[19][20][21] Numerous studies have focused on the use of DCE-MRI as a tool for evaluating bone marrow in hematologic malignancies. 19,20,[22][23][24] Chen et al evaluated the use of DCE-MRI of bone marrow as a predictor of survival for patients with acute myeloid leukemia who were clinically in complete remission and found that the perfusion kinetics of the bone marrow were an indicator of survival. 24 More recently, DCE-MRI has been suggested as a tool to help differentiate acute, subacute, and chronic metastatic lesions.…”
Section: Gadolinium Contrast-enhanced Mrimentioning
confidence: 99%
“…1,2 The role of imaging studies in the treatment of MM includes assessment of the extent of the severity of the disease at presentation, and identification and characterization of complications, as well as the subsequent stage of the disease. [3][4][5][6][7] Compression fractures increase morbidity and mortality, causing spinal deformity and intractable pain. Clinical studies of vertebroplasty (VP) have reported a 90% reduction of pain, with minimal complications, which is relatively high.…”
mentioning
confidence: 99%